2022
DOI: 10.1111/andr.13199
|View full text |Cite
|
Sign up to set email alerts
|

4BNT162b2 mRNA COVID‐19 vaccine and semen: What do we know?

Abstract: Background:The effects of an mRNA COVID-19 vaccine on spermatozoa parameters are not known. The aim of this study was to evaluate the effect of the BNT162b2 mRNA COVID-19 vaccine on human semen, comparing spermatozoa parameters before and after vaccine inoculation. Materials and methods:In this single-center prospective study, voluntary subjects who received mRNA vaccines from February to July 2021 were enrolled. The study population included male subjects aged between 18 and 45 years who completed the BNT162b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Moreover, five prospective studies were performed, four of which on healthy young volunteers/sperm donor men ( 93 , 95 , 97 , 98 ), and one on men undergoing IVF (for female infertility factors) ( 102 ). Overall, no significant alterations of sperm parameters were observed, except in the study by Abd et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, five prospective studies were performed, four of which on healthy young volunteers/sperm donor men ( 93 , 95 , 97 , 98 ), and one on men undergoing IVF (for female infertility factors) ( 102 ). Overall, no significant alterations of sperm parameters were observed, except in the study by Abd et al.…”
Section: Resultsmentioning
confidence: 99%
“…Male fertility after COVID-19 vaccination has been assessed in one case report (90) (Supplementary Table S1) and 11 clinical studies (91,(93)(94)(95)(96)(97)(98)(99)(100)(101)(102), as shown in Supplementary Table 2.…”
Section: Male Reproductive Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…No effects on semen parameters have been described [91][92][93][94] It should be reminded that most evidence is derived from the use of these drugs in other pathologies Endocrine semen parameters in vivo [69,70]. Another drug, remdesivir, has minimal data available for male fertility but is with no relevant adverse effects in pregnant women [71].…”
Section: Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…An internetbased study demonstrated that, after approval of vaccinations by health authorities, queries on fertility effects of SARS-CoV-2 vaccination increased dramatically [90], reflecting fears of many young adults of reproductive age, despite the lack of a solid theoretical link. However, the few available papers concur that no effects on semen parameters, oxidative stress and seminal plasma IL-6 are present [91][92][93][94]. A recent meta-analysis of these studies reported that in healthy volunteers receiving mRNA-based vaccines, no significant negative effect on sperm concentration motility and semen volume was observed, while data on sperm morphology was unavailable [4].…”
Section: Vaccinationmentioning
confidence: 99%